EVALUASI KINERJA SIMPANG BERSINYAL DAN PENGATURAN ULANG WAKTU SIKLUS APILL MENGGUNAKAN PTV VISSIM - Ivana Pantulu; Yuliyanti Kadir; Frice Lahmudin Desei (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2025)
The signalized intersection of Jalan Raja Eyato - Moh. Yamin A.R. Koniyo serves as a connection between commercial areas, tourist attractions, fast-food restaurant zones, and religious sites. As a result, this intersection experiences heavy traffic flow. Additionally, its asymmetric/weaving geometric design extends travel time from one approach to another. This study aims to evaluate the intersection's performance and level of service using the Indonesian Highway Capacity Guidelines (PKJI) 2023 and simulation modeling with PTV Vissim Student Version. The analysis results based on PKJI 2023 show the delay values as follows: Jalan Moh. Yamin at 49 seconds with level of service E, Jalan A.R. Koniyo at 38,1 seconds with level of service D, Jalan Raja Eyato (west) at 49,5 seconds with level of service E, and Jalan Raja Eyato (east) at 33,6 seconds with level of service D. The average intersection delay is 37 seconds, classified as level of service D. Meanwhile, the simulation results using PTV Vissim Student Version indicate delay values of 73,4 seconds with level of service E for Jalan Moh. Yamin, 72 seconds with level of service E for Jalan A.R. Koniyo, 46,3 seconds with level of service D for Jalan Raja Eyato (west), and 27,8 seconds with level of service C for Jalan Raja Eyato (east), with an average intersection delay of 54,5 seconds with level of service D. Four alternative solutions were proposed to improve the intersection's performance. The best solution is Alternative 2. which reduced signal phases four to three. This adjustment reduced delays by approximately 33% compared to current conditions, without requiring additional infrastructure costs.